Validity and reliability of “Short-questionnaire of tuberculosis patients’ knowledge about anti-tuberculosis and hepatotoxicity” (SQ-KSH-TB) - Dyah Aryani Perwitasari; Muh. Deni Kurniawan; Lalu Muhammad Irham; Imaniar Noor Faridah; Triantoro Safaria; Woro Supadmi; Didik Setiawan; Triantoro Safaria (Pharmaciana, 2023)
Until presently, tuberculosis has been a burden to Indonesia, placing the country third among countries with the heaviest tuberculosis burden in the world. Tuberculosis treatment takes a long period and may cause side effects. Therefore, it requires sufficient tuberculosis knowledge on the patients' part for the patients to know of the side effects of anti-tuberculosis and how to deal with them. This research aimed to obtain a short questionnaire of tuberculosis patients' knowledge about anti-tuberculosis and hepatotoxicity (SQ-KSH-TB) which determines patients' knowledge of anti-tuberculosis side effects and how to handle them. This research employed a cross-sectional design and involved 17 public health services (puskesmas) and three hospitals in Yogyakarta Province. The inclusion criteria were patients diagnosed with pulmonary tuberculosis and being in a tuberculosis treatment period with a public health service or a pulmonary hospital in Yogyakarta Province. The exclusion criteria were the patients passing away, having completed a six months treatment or having been receiving treatment for over six months, and being unwilling to cooperate in the research. The questionnaire used in this research was a questionnaire that was developed based on prior research work, containing eight questions on a Guttman scale. Validity and reliability analyses were carried out with Pearson's product-moment correlation and the Kuder-Richardson-20 test, respectively. As many as 194 subjects enrolled in this research. The eight questions in the questionnaire had r count values greater than the r table, hence meeting the validity criterion. Meanwhile, the KR-20 value obtained was 0.721, indicating a good level of reliability. The SQ-KSH-TB was able to meet the validity and reliability criteria, showing applicability in the Indonesian context.